Impact of two typhoons on the marine environment in the Yellow Sea and East China Sea - 付东洋 栾虹 潘德炉 张莹 王立安 刘大召 丁又专 李薛 (Chinese journal of oceanology and limnology, 2016)
This study investigated the ef fects of two typhoons（Nari and Wipha） on sea surface temperature（SST） and chlorophyll- a（Chl- a） concentration. Typhoons Nari and Wipha passed through the Yellow Sea on September 13, 2007 and the East China Sea（ECS） on September 16, 2007, respectively. The SST and Chl- a data were obtained from the Aqua/Terra MODIS and NOAA18, respectively, and the temperature and salinity in the southeast of the study area were observed in situ from Argo. The average SST within the study area dropped from 26.33°C on September 10 to a minimum of 22.79°C on September 16. Without the usual phenomenon of ‘right bias’, the most striking response of SST was in the middle of the typhoons’ tracks, near to coastal waters. Strong cooling of the upper layers of the water column was probably due to increased vertical mixing, discharge from the Changjiang River estuary, and heavy rainfall. During the typhoons, average Chl-a increased by 11.54% within the study area and by 21.69% in the off shore area near to the southeast ECS. From September 1 to 13, average Chl-a was only 0.10 mg/m~3 in the of fshore waters but it reached a peak of 〉0.17 mg/m~3 on September 18. This large increase in Chl-a concentration in of fshore waters might have been triggered by strong vertical mixing, upwelling induced by strong typhoons, and sedimentation and nutrient infl ux following heavy rainfall.